Gut microbiota-dependent anti-inflammatory mechanisms of berberine in ameliorating hypertension: role of SCFAs, LPS reduction, and STAT3 signaling - Wang, Shanshan; Hu, Yaqian; Li, Xin; Ou, Yanhua; Chen, Jinling; Chen, Yuhan; Chen, Jingyi; Bai, Kunran; Xu, Fangwen; Wang, Xingyi; Du, Haoming; Yuan, Difen; et al. (Frontiers in Pharmacology, 2026)
BackgroundHypertension is a chronic disease closely related to vascular remodeling, inflammatory response and intestinal flora disorders. Traditional Chinese medicines, especially Rhizoma Coptidis, are becoming increasingly popular as a possible cardioprotective drug. Berberine, the main active ingredient of Rhizoma Coptidis, has various pharmacological activities, but its specific mechanism of regulating blood pressure through intestinal flora is not clear.MethodsIn this study, the potential targets of berberine were predicted using network pharmacology, and its antihypertensive mechanism was validated in spontaneously hypertensive rats (SHR). A comprehensive evaluation integrating non-invasive blood pressure measurement, echocardiography, histological analyses (H&E and Masson staining), immunohistochemistry, qPCR, metagenomic sequencing, and untargeted metabolomics was performed to investigate the effects of berberine on cardiovascular remodeling, intestinal barrier integrity, gut microbial composition, and metabolic profiles.ResultsNetwork pharmacology screened 160 common targets of berberine and hypertension, among which STAT3 may play a key role. Animal experiments confirmed that berberine significantly reduced SHR blood pressure and improved aortic fibrosis and cardiac function. In addition, berberine repaired intestinal barrier damage, upregulated ZO-1 and Occludin expression, and significantly altered the structure of the intestinal flora, increasing the abundance of Short-chain fatty acids (SCFAs) - producing bacteria (e.g., Marvinbryantia, Bacteroides), while decreasing pro-inflammatory bacteria (e.g., Mycoplasma, Treponema). Metabolomics analysis showed that berberine increased fecal SCFAs levels and decreased serum Lipopolysaccharide (LPS). Molecular docking and experimental validation showed that berberine attenuated the inflammatory response by inhibiting STAT3 activation and decreasing colonic IL-6 expression.ConclusionBerberine exerts antihypertensive effects by regulating the gut flora-SCFAs-LPS-IL6-STAT3 axis, improving intestinal barrier function, and reducing systemic inflammation. This study provides a new mechanistic basis for berberine treatment of hypertension.